DA’WAH IN THE ERA OF ARTIFICIAL INTELLIGENCE: AN ETHICAL ANALYSIS OF ISLAMIC COMMUNICATION ON THE USE OF AI IN THE PRODUCTION OF RELIGIOUS MESSAGES - Aritonang, Idris; Br. Barus, Liza Nuarida Ulfah; Rubino (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2026)
The rapid development of Artificial Intelligence (AI) in the digital era has significantly transformed various fields, including religious communication and the production of da’wah messages. AI technologies such as automated content generation, algorithmic curation, chatbots, voice synthesis, and visual media have enabled da’wah activities to become more efficient, interactive, and far-reaching. However, the increasing use of AI in religious contexts also raises ethical concerns related to the authenticity of religious messages, scholarly authority, moral responsibility, and the potential distortion of Islamic teachings. This study aims to examine the use of AI in the production of religious messages from the perspective of Islamic communication ethics. Employing a qualitative descriptive library research method, this study analyzes primary and secondary sources, including the academic books, and reputable scholarly journals. The data were examined using content analysis and normative-interpretative approaches, focusing on Islamic communication principles such as qaulan sadīdan, qaulan balīghan, qaulan karīman, qaulan ma‘rūfan, qaulan layyinan, and qaulan maisūran. The findings indicate that AI can serve as an effective supporting tool for da’wah when guided by Islamic ethical values and human supervision. However, without proper ethical control, AI-based da’wah risks compromising the integrity, credibility, and spiritual essence of Islamic communication. This study contributes to the development of ethical frameworks for da’wah practices in the era of intelligent technology